A Concise Total Synthesis of (±)-Camptothecin - Liu, Qian; Huang, Guan-xin; Liu, Min-jie; Chen, Fen-Er (Synthesis, 2019)
A total synthesis of racemic camptothecin, characterized by a concise construction of the ring systems and easy functional group transformation, is described. A domino reaction consisting of a Heck reaction and an aza-intramolecular Michael addition to form the C ring serves as the first key step in the synthesis. The D ring was constructed by a simple Wittig–Horner reaction followed by removal of the protective groups. Hydroxymethylation, demethylation, and lactone formation reactions were performed in one-pot to construct the E ring under hydrobromic acid conditions. This work provides an efficient scheme for further synthetic exploration of camptothecin and its analogues.
Keywords: camptothecin; total synthesis; domino reaction; Heck reaction